Locus of control in alcohol dependent patients in remission - Pektaş, Özkan; Mırsal, Hasan; Kalyoncu, Ö. Ayhan; Tan, Devran; Beyazyürek, Mansur (Journal of Dependence, 2003)
Objective: Locus of control is a personality construct referring to an individual’s perception of the locus of events. In this study, the correlation of locus of control with various sociodemographic clinical characteristics was investigated in alcohol dependent patients in remission.Method: 102 patients who fulfilled DSM-IV criteria of alcohol dependence and were hospitalized and treated for alcohol dependence before but in remission for at least 6 months were included. Patients who had comorbid psychiatric disorders, and took any psychotropic medication in the last one month were excluded. Measures included sociodemographic data form, Rotter’s Internal-External Locus of Control Scale(RIELCS), Hamilton Depresion Rating Scale-17(HAM-D-17), and State-Trait Anxiety Inventory(STAI). All information was analyzed by SPSS (Windows 6.0) program.Results: The study subjects were 17 female patients (16.6%) and 85 male patients (83.4%). The mean age of the study group was 44.5 (sd=6.1). RIELCS showed significant differences between two genders (F=11.7; p
Keywords: Alcohol dependence; locus of control; sociodemographic-clinical characteristics